A Midwestern Academic HIV Clinic Operation during the COVID-19 Pandemic: Implementation Strategy and Preliminary Outcomes. (2nd September 2021) - Fadul, Nada; Regan, Nichole; Kaddoura, Layan; Swindells, Susan
During the COVID-19 pandemic, HIV clinics had to transform care delivery for people with HIV (PWH). We developed a multifaceted telehealth implementation strategy and monitored number of out of care patients (OOC), medical visit frequency (MVF), gap in care (GiC) and viral suppression (VS), and compared measures to baseline data. Between April and October 2020, 1559 visits were scheduled; 328 (21%) were missed, and 63 (4%) were new to care. Of the remaining 1168 follow-up visits, 412 (35%) were telehealth visits. As of October 2020, there were 53 patients OOC, MVF was 55% and GiC was 24% compared to 34, 69% and 14% at baseline, respectively. Overall VS rate remained high at 93% (97% for telehealth and 91% for in-person visits, p = 0.0001). Our implementation strategy facilitated quick provision of telehealth to a third of PWH receiving care in our clinic. While MVF decreased and GiC increased, VS rates remained high.